The development of green building in China and an analysis of the corresponding incremental cost: A case study of Zhejiang Province - J. Ge; J. T. Weng; K. Zhao; X. C. Gui; P. Li; M. M. Lin (International Association of Lowland Technology, 2018)
With a focus on the survey of the green building development in China as well as the evaluation of the corresponding incremental cost, this paper selects 276 green building projects in Zhejiang Province and obtains comprehensive data, based on which the development of green buildings in the province is analysed. The results are then compared with the national data in such aspects as the certification grade, building type, geographical distribution and application frequency of green building technologies. Statistical analyses are also conducted on the technology application frequency and the incremental cost, which conclude that different types of green buildings would apply significantly different technologies considering factors like energy saving, material saving, indoor environment quality and operational management. According to the sample data, the incremental cost of green building technologies is found to make up less than 2% of the total building costs; and it increases with the upgrading of certification grade. When the floor area exceeds 100,000 square meters, the incremental cost would remain less than 60 yuan per square meters. Costs for water-saving and energy-saving technologies account for over 80% of the total incremental cost. This study would provide guidance for the selection of green building technologies.